The History of FKUB in The Development of Character Education for Religious Communities in Sidoarjo - Kamaliah, Nailah; Fitriany, Aulia; Mubarok, M. Khusni; Widodo, J. Priyanto (IAIN Madura, 2024)
This study aims to explain how the history of the establishment of the Forum Kerukunan Umat Beragama (FKUB) or Religious Harmony Forum, how the development of character education and what roles are performed by FKUB. It uses a historical method with a case study approach, including collecting information through interviews, archival documents, observation, and documentation. The results of the study state that the FKUB of Sidoarjo Regency functions as a regular forum for religious leaders and community leaders to strengthen relations between religious communities. The government established FKUB to maintain inter-religious harmony and ensure a harmonious society, in accordance with PBM No. 9 and 8 of 2006. In Character Education Development, it is also important to instil positive values such as integrity, cooperation and responsibility. FKUB also has a significant role in shaping positive and healthy community views, responding to misleading issues, accommodating the aspirations of religious organisations and providing advice regarding the construction of houses of worship. The data shows that the percentage increase in the number of mosques in Sidoarjo from 2021 to 2022 is around 4.47%.